Game Design and Intelligent Interaction - Deliyannis, Ioannis (IntechOpen, 2020)
The book presents a collection of chapters that focus on the design, use, and evaluation of games and the application of gamification processes in serious learning scenarios. This is clearly the way of the future, as those technologies are currently being used to change the way we explore, learn, and share our knowledge with others. The field will evolve in the near future with the use of new delivery platforms, while various technologies will merge into more concrete media, including wearable multipurpose devices. This book presents a series of design and evaluation case studies enabling the reader to appreciate the complexity of the task in hand, sample different case studies, and appreciate how different requirements can be met using game design and evaluation theory, analysis, and implementation.